Two-dimensional magneto-optical trap of dysprosium atoms as a compact source for efficient loading of a narrow-line three-dimensional magneto-optical trap - Jin, Shuwei; Gao, Jianshun; Chandrashekara, Karthik; Gölzhäuser, Christian; Schöner, Joschka; Chomaz, Lauriane (Physical review. A, Atomic, molecular, and optical physics, 2023)
We report on a scheme for loading dysprosium atoms into a narrow-line three-dimensional magneto-optical trap (3D MOT). Our approach replaces the conventional Zeeman slower with a two-dimensional (2D) MOT operating on the broad 421-nm line to create a high-flux beam of slow atoms. Even in the absence of a push beam, we demonstrate efficient loading of the 3D MOT, which operates on the narrower 626-nm intercombination line. Adding push beams working at either 421 nm or 626 nm, significant enhancement of the loading rate is achieved. We reach the best performance, with an enhancement factor of 3.6, using a push beam red-detuned to the 626-nm line. With loading rates greater than 108atoms/s achieved at a moderate oven reservoir temperature of 800∘C, our method offers similar or greater performance than Zeeman-slower-based systems. Our 2D-MOT-based approach constitutes a promising first step towards state-of-the-art quantum gas experiments with several advantages over the Zeeman-slower-based setup and is readily adaptable to other open-shell lanthanides.
Gesehen am 14.09.2023